Studies on reactions of oxidizing sulfur–sulfur three-electron-bond complexes and reducing α-amino radicals derived from OH reaction with methionine in aqueous solution - Lu, Changyuan; Yao, Side; Lin, Nianyun (Biochimica et biophysica acta, 2001)
The technique of pulse radiolysis with spectrophotometric detection has been used to investigate the possibility of electron transfer reactions between oxidizing sulfur–sulfur three-electron-bond complexes (Met 2/S∴S +), or reducing α-amino radicals (CH 3SCH 2CH 2CH ⋅NH 2) derived from reaction of methionine with OH radicals and hydroxycinnamic acid (HCA) derivatives, riboflavin (RF) or flavin adenine dinucleotide (FAD), respectively. The HCA derivatives, such as caffeic acid, ferulic acid, sinapic acid and chlorogenic acid, widely distributed phenolic acids in fruit and vegetables, have been identified as good antioxidants previously can rapidly and efficiently repair oxidizing three-electron-bond complexes via electron transfer. RF and FAD can oxidize reducing α-amino radicals derived from methionine. The electron transfer rate constants ∼10 9 dm 3 mol −1 s −1 were determined by following the build-up kinetics of species produced.